2018
DOI: 10.1111/dom.13369
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous GLP‐1 alters postprandial functional connectivity between homeostatic and reward‐related brain regions involved in regulation of appetite in healthy lean males: A pilotstudy

Abstract: This pilot trial provides preliminary experimental evidence that glucose-induced endogenous GLP-1 affects central regulation of appetite by modulating rsFC in homeostatic and reward-related brain regions in healthy lean male participants in a GLP-1 receptor-mediated fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 41 publications
1
8
0
1
Order By: Relevance
“…With our exploratory fMRI sub-study, we were not able to reinforce this hypothesis. Specifically, we did not observe altered resting state functional connectivity between homeostatic and reward-related brain areas on GLP-1 RA, as previously showed in healthy volunteers by Meyer-Gerspach et al (37).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…With our exploratory fMRI sub-study, we were not able to reinforce this hypothesis. Specifically, we did not observe altered resting state functional connectivity between homeostatic and reward-related brain areas on GLP-1 RA, as previously showed in healthy volunteers by Meyer-Gerspach et al (37).…”
Section: Discussionsupporting
confidence: 88%
“…Functional connectivity of three key regions of the reward network (left accumbens, right accumbens, midbrain) and the hypothalamus (see supplementary figure S9) with the rest of the brain was assessed during the resting-state session (37). In patients, the main effect of treatment on functional connectivity values was tested with the hypothesis that functional connectivity between those core regions and other regions of the reward network would be altered on dulaglutide, as compared to placebo (37). Similarly, functional connectivity of those regions was compared between patients under placebo and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Both PYY and GLP-1 levels are elevated in the postprandial state following bariatric surgery ( 44 ), while fasting ghrelin levels have been shown to decline postoperatively ( 45 ). ten Kulve et al ( 46 ) reported that the GLP-1 analog exenatide promotes hypothalamic activity in humans and hypothalamic connectivity with the rest of the brain, and Meyer-Gerspach et al ( 47 ) extended this to the action of endogenous GLP-1, revealing that administration of the GLP-1 receptor antagonist exendin(9-39) disrupted functional connectivity between homeostatic (hypothalamus) and reward-related (OFC) brain regions. More recently, another study by ten Kulve et al ( 48 ) showed that in 10 obese females undergoing RYGB, activation was reduced in the caudate nucleus in response to food and that this was interrupted after RYGB with GLP-1R blockade.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on resting‐state functional connectivity alterations in response to GLP‐1 receptor blockade is scarce. One study in males showed that blocking GLP‐1 receptors after ingestion of a glucose load resulted in increased connectivity with the amygdala and orbitofrontal cortex, but lower connectivity with the caudate nucleus compared with ingestion of a glucose load without GLP‐1 receptor blockade 9 . Bariatric surgery has also been shown to affect intrinsic functional connectivity, albeit literature reporting this is scarce.…”
Section: Introductionmentioning
confidence: 99%